Performance characteristics of Filipino collegiate athletes (2014)
Aside from well-developed motor skills, a high level of performance-related fitness is often a prerequisite for successful participation in sports. This study identified the performance characteristics of Filipino collegiate athletes (n=158) according to gender and type of sport. Performance measures were administered to 158 collegiate athletes and and a 2-way (gender x type of sport) MANOVA was used to assess the differences between groups. Results showed no gender x type of sport interaction as well as type of sport main effect, but there was gender effect. Varsity males were taller (1.70=0.07 m vs. 1.58 = 0.07 m, eta2 = 0.459) heavier (67.84 = 13.24 kg vs. 54.83 = 8.87 kg, eta2 - 0.254) have less body fat (85.11 = 43.07 mm vs. 117.49 = 30.06 mm, eta2 = 0.648) and better cardiovascular endurance (45.76 = 8.46 ml.kg. min vs. 34.92 = 5.86 ml.kg.min, eta2 = 0.372) than their female counterparts. In comparison to Caucasian athletes, Filipino players are shorter, lighter, have lower aerobic capacity, leg power, and flexibility. However, performance characteristics of Filipino are still varied when compared with neighboring Asian countries. Nonetheless, Filipino variety athletes should focus on improving their fitness to be at par with those of neighboring countries by developing training programs and adhering to a more periodized practice schedules throughout the season.
Keywords: Athletes; Sports